2013
DOI: 10.1111/jdi.12183
|View full text |Cite
|
Sign up to set email alerts
|

Changes in oral antidiabetic prescriptions and improved glycemic control during the years 2002–2011 in Japan (JDDM32)

Abstract: Aims/IntroductionSix kinds of oral antidiabetic drugs (OADs), including the new dipeptidyl peptidase 4 (DPP‐4) inhibitors, are available. The present study aimed to define trends within the prescribing patterns of OADs, as well as changes in glycemic control in Japan over a 10‐year period from 2002 to 2011.Materials and MethodsWe carried out a cross‐sectional study using data of type 2 diabetes mellitus patients from 24 clinics for 2002, 2005, 2008 and 2011. OAD use was analyzed combined with clinical data.Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
81
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(88 citation statements)
references
References 30 publications
7
81
0
Order By: Relevance
“…The study documented higher number of DPP-4 inhibitors such as vildagliptin (9.52%) prescribed. DPP-4 inhibitors use has greatly increased with uncontrolled overweight/obese; this result is in agreement with other reports conducted worldwide [12][13][14]. Another study carried out by Tolba et al, vildagliptin as an add-on therapy to gliclazide was not associated with the cardiovascular risks and showed the significant reduction in the hemoglobin A1c and fasting blood sugar [15].…”
Section: Geetha and Shanmugasundharamsupporting
confidence: 81%
“…The study documented higher number of DPP-4 inhibitors such as vildagliptin (9.52%) prescribed. DPP-4 inhibitors use has greatly increased with uncontrolled overweight/obese; this result is in agreement with other reports conducted worldwide [12][13][14]. Another study carried out by Tolba et al, vildagliptin as an add-on therapy to gliclazide was not associated with the cardiovascular risks and showed the significant reduction in the hemoglobin A1c and fasting blood sugar [15].…”
Section: Geetha and Shanmugasundharamsupporting
confidence: 81%
“…When compared to patients who planned to start first-time insulin therapy [15] or those using oral hypoglycemic agents (OHA) alone [16], the following features were observed in this cohort: better glycemic control than patients considering insulin injections [15], but not better than those using OHA alone [16]; younger; shorter duration of T2DM; and higher BMI [19]. With regard to high BMI, obese T2DM patients with poor glycemic control in OHA therapy seemed to have been selected as candidates for this study in the hope of weight loss via liraglutide [17].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies surveying the control status of lipids and BP in Japanese patients have been reported [12][13][14][15] ; however, these studies targeted only those who had been taking medications for lipids or BP, suggesting that the results of these studies do not reflect the overall control status including those who are not on medication. The Japan Diabetes Clinical Data Management (JDDM) Group has been analyzing the status of glycemic control in diabetic patients since 2002 16) ; however, at present, no such data have been available in subjects with pCHD and pCVD in Japan. The Ministry of Health, Labour and Welfare of the Japanese government annually performs National Health and Nutrition Examination Survey by randomly selecting approximately 6,000-10,000 subjects from the general Japanese population and releases the data on its homepage 17) ; however, understandably, no data are available on the control status in those who are at high risk of atherosclerotic diseases.…”
Section: Discussionmentioning
confidence: 99%